Valuation of human capital : quantifying the importance of an assembled workforce - Merriman, Kimberly K. (Springer International Publishing, 2017)
This book addresses the gap between the espoused importance of organizational human capital and how it is actually reported and assessed. It also discusses the current and potential uses of human capital measurement and a way for HR to position itself among other business functions such as finance, accounting, and operations. Readers will finish with an understanding of approaches for the valuation of a firm's human capital, practical applications for the economic analysis of human capital, and gaps that are ripe for research and practice to address.
8.3 How Organizational Social Capital Enhances Human Capital Value.
Keywords: Human capital.; Business.; Leadership.; Personnel management.; elektronické knihy; electronic books